Gas Quality Impact on Gas Engine Performance: Case of an Indonesia Natural Gas Station - Rizki Wijanarto Budiman; Riman Sipahutar (International Journal Labs, 2023)
This research was conducted to find a correlation between changes in the variable composition of the natural gas fuel in gas engine generators, and the occurrence of a unit shutdown at a natural gas distribution facility in South Sumatra-Indonesia. The analysis is carried out by investigating the trend of changes in gas composition parameters, and simulation using the Methane Number Calculator application. The results obtained from the research results, in Changes in the composition of fuel gas cause changes in the methane number, Low Heating Value (LHV), High Heating Value (HHV), and Wobbe index (WI), which may indicate engine trouble and cause a unit shutdown. Several options of solutions can be carried out as discussions to solve problems that occur in the gas engine generator at the natural gas distribution facility